Reservation and the Republic: One Constitution, Two Amendments and Seven Decades. (September 2019) - Deshpande, Satish
This note places the recent 103rd Amendment of the Constitution for introducing 10 per cent reservation for 'economically weaker' sections of the upper castes in the larger context of the ongoing effort to redress caste inequalities in law. It compares this amendment to the First Amendment to the Constitution of 1951 and argues that these two amendments describe a full circle. The law seems to have moved from a stance where castelessness was the explicit norm and caste the exception to one where caste identities are now treated as the implicit norm. The note also points to possible routes for legal challenges to this amendment and underlines the Constitution's continuing refusal – or inability – to deal with caste directly.